Emotional Intelligence and the Process of Education in Nigeria (2023)
The process of education is designed to achieve certain goals of the society, which can be done through some factors considered important. These factors include emotion and intelligence. Emotion is an important component of educational process, which involves perception, comprehension and management of strong feelings. Failure to manage emotion properly can result in negative consequences. Intelligence, on the other hand, is also essential in the teaching/learning process. Therefore, emotional intelligence is an important factor in the education process. It is one of the factors that are indispensable in cordial human relationships. Emotional intelligence can be described as the ability to comprehend or perceive any strong feeling intelligently The Nigerian society is beset with various forms of social vices which are attributed to deficiencies in emotional intelligence. This study examined emotional intelligence as a concept in the process of education. Education is an agency in a society responsible for offering Solutions to problems. For several decades, it has done this to a successful extent in Nigeria, but there is still much to do The concept of emotional intelligence was analysed with its implications on the Nigerian educational System The paper employed the philosophical research method of speculation, analysis and prescription to find out that learners are to be groomed through the process of education to be emotionally intelligent. The paper concluded that the media is essential in achieving this aim and therefore, needs to be censored, as it is an important agent that influences learners